Time-optimal Trajectory Planning of Robot based on Breed Algorithm - Yu Rui; Wang Chengjun; Guo Yongcun; Zhang Yuping (Jixie chuandong)
With the 6-DOF manipulators of the multi-arm casting robot as the research object,the trajectory planning is designed by the 4-3-4 polynomial interpolation method in the joint space. Under the constraint of velocity,the breed algorithm is used to optimize the interpolation results to obtain the optimal motion time of manipulator. Contrast to the particle swarm optimization,the breed algorithm has the higher precision and more rapid speed in the convergence procedure. By means of the Matlab,the movement position,velocity and acceleration curve of each joint of the dual arm robot are obtained. The consequence shows this method can accurately realize the time optimal trajectory planning at the speed constraint.